2008
DOI: 10.1073/pnas.0709807104
|View full text |Cite
|
Sign up to set email alerts
|

Different phosphorylation states of the anaphase promoting complex in response to antimitotic drugs: A quantitative proteomic analysis

Abstract: The anaphase promoting complex (APC) controls the degradation of proteins during exit from mitosis and entry into S-phase. The activity of the APC is regulated by phosphorylation during mitosis. Because the phosphorylation pattern provides insights into the complexity of regulation of the APC, we studied in detail the phosphorylation patterns at a single mitotic state of arrest generated by various antimitotic drugs. We examined the phosphorylation patterns of the APC in HeLa S3 cells after they were arrested … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
96
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(100 citation statements)
references
References 26 publications
3
96
1
Order By: Relevance
“…Nevertheless, the phosphopeptide signal was higher in all of the R light than the dark samples, and peptide-level quantification from other peptides indicated that the overall PIF3 levels were lower in the R light samples, suggesting that this site may also be induced by R light. A second method of calculating phosphorylation changes employed ratios between detected signal intensities of phosphorylated and unphosphorylated peptides (bottom panel in Supplemental Figure 1C online) (Steen et al, 2008). The results from this analysis are also presented in Supplemental Data Set 1 and Supplemental Table 2 online and generally agreed with those determined using the percentage phosphopeptide signals.…”
Section: Light Induces Multisite Phosphorylation Of Pif3 In Vivosupporting
confidence: 70%
See 1 more Smart Citation
“…Nevertheless, the phosphopeptide signal was higher in all of the R light than the dark samples, and peptide-level quantification from other peptides indicated that the overall PIF3 levels were lower in the R light samples, suggesting that this site may also be induced by R light. A second method of calculating phosphorylation changes employed ratios between detected signal intensities of phosphorylated and unphosphorylated peptides (bottom panel in Supplemental Figure 1C online) (Steen et al, 2008). The results from this analysis are also presented in Supplemental Data Set 1 and Supplemental Table 2 online and generally agreed with those determined using the percentage phosphopeptide signals.…”
Section: Light Induces Multisite Phosphorylation Of Pif3 In Vivosupporting
confidence: 70%
“…This value is compared directly for dark control and R light-treated seedlings at each site in Figure 1D. In the second method, a value termed the relative phospho ratio was defined as the ratio of two values, each of which are themselves ratios (Steen et al, 2008). In this procedure, the ratio of the abundance of phosphorylated to nonphosphorylated residues, detected at a given site, is calculated separately for dark control and R-treated seedlings, and then the ratio of these two derived values is expressed as the ratio of R to dark values (see Supplemental Figure 1C, bottom panel, Supplemental Data Set 1, and Supplemental Table 2 online).…”
Section: Identification Of Phosphorylation Sites and Quantificationmentioning
confidence: 99%
“…Protein/peptide identification, the phosphorylation site assignment, as well as information on the relative stoichiometry were obtained from two LC-MS/MS experiments with nonphosphorylated (control) and phosphorylated (sample) preparations (40,41). Briefly, two samples were prepared as described under the CYP3A4 phos-phorylation assay (11).…”
Section: Methodsmentioning
confidence: 99%
“…Protein/peptide identification, the phosphorylation site assignment, as well as information on the relative stoichiometry can be obtained from two LC-MS/MS experiments with unphosphorylated (control) and phosphorylated (sample) preparations (65,66).…”
Section: ␥-S-[mentioning
confidence: 99%